Sharing risks. On social risk management and the goverance of labour market transitions - Schmid, Günther (Berlin, 2006)
"This is a paper based on the annual lecture in honour of Hugo Sinzheimer at November 10, 2005, Hugo-Sinzheimer-Institute at the University of Amsterdam. In 1928, Sinzheimer wrote an article entitled “Die Demokratisierung des Arbeitsverhältnisses,” (The Democratisation of the Employment Relationship). His references to unemployment insurance that had been enacted just one year earlier went beyond the participation of trade unions and employers in administration as an essential element of democratization. Sinzheimer put even more emphasis on another aspect of democratization, namely, the enlargement of the risksharing community to embrace all workers, indeed, the whole economy. The argument of the paper is that sharing risks through universal and state-guaranteed unemployment insurance is still as valid as in the time of Hugo Sinzheimer. There is no reason to roll back the welfare state. On the contrary, there are strong reasons to defend the principle of social insurance. By combining a kind of work-life insurance with soft forms of governance, this principle—that of “sharing risks”— can even be extended to include the new risks related to critical events during the life course. The argument is developed by answering the following questions: First, what are the new risks to which established insurance systems have to respond? Second, what are the advantages of social insurance compared to private savings? Third, how should we share for example the risks related to parenting and to continuing education and training? Fourth, how do we overcome risk-aversion to stimulate more individual risk-taking and thereby more responsibility?"